2011
DOI: 10.1007/s10735-011-9359-x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal expression of VEGF and its receptors 1 and 2 in post-traumatic bone bridge formation of the growth plate

Abstract: Injuries to growth plates may initiate the formation of reversible or irreversible bone-bridges, may leading to bone length discrepancy or axis deviation. As vascular invasion is essential for the formation of bone tissue, the aim of our study was to investigate the kinetic expression of Vascular Endothelial Growth Factor (VEGF) and its receptors R1 and R2 and the ingrowth of vessels in the formation of bone bridges in a rat physeal injury model. Quantitative Real-Time Polymerase Chain Reaction was performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…During the osteogenic phase of the growth plate injury repair process, the cells within the fibrogenic infiltrate differentiate into Runx2 and alkaline phosphatase-immunopositive osteoblasts , Arasapam et al 2006, Chung et al 2006 and produce increased levels of bone matrix protein osteocalcin (both mRNA and protein) during days 8-14 , Arasapam et al 2006. Similarly, Fischerauer et al (2011) also observed collagen-1-immunopositive bone tissue at the injury site w14 days post-growth plate injury (Fischerauer et al 2011). On day 35, histologic examination of the injury site has also revealed the presence of flattened inactive bone-lining osteoblasts that weakly expressed osteocalcin .…”
Section: The Osteogenic and Remodelling Phasesmentioning
confidence: 98%
See 2 more Smart Citations
“…During the osteogenic phase of the growth plate injury repair process, the cells within the fibrogenic infiltrate differentiate into Runx2 and alkaline phosphatase-immunopositive osteoblasts , Arasapam et al 2006, Chung et al 2006 and produce increased levels of bone matrix protein osteocalcin (both mRNA and protein) during days 8-14 , Arasapam et al 2006. Similarly, Fischerauer et al (2011) also observed collagen-1-immunopositive bone tissue at the injury site w14 days post-growth plate injury (Fischerauer et al 2011). On day 35, histologic examination of the injury site has also revealed the presence of flattened inactive bone-lining osteoblasts that weakly expressed osteocalcin .…”
Section: The Osteogenic and Remodelling Phasesmentioning
confidence: 98%
“…Previously, TNFa has been associated with bone remodelling by promoting osteoclast differentiation (Horowitz et al 2001). In addition, Fischerauer et al (2011) have also observed an increase in expression of VEGF (VEGFA) (Fischerauer et al 2011). VEGF has known roles not only in angiogenesis but also in osteoblast differentiation and osteoclast recruitment .…”
Section: The Osteogenic and Remodelling Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…While a recent study has observed the expression of VEGF and its receptors during growth plate injury repair with a similar spatial and temporal pattern to that in bone fracture repair (Fischerauer et al 2011), the role of VEGF in the angiogenesis and the bony repair of the injured growth plate remains unknown. In the current study, it is proposed that VEGF is critical for the angiogenesis and bony repair within the growth plate injury site, and that blocking of VEGF will decrease the undesirable bony repair tissue following growth plate injury.…”
Section: Introductionmentioning
confidence: 96%
“…Being a cartilage scaffold, the growth plate remains the weakest part of a long bone and hence prone to injury (Mizuta et al 1987). Following an injury, the growth plate is often repaired by an 'unwanted' bony tissue (also called a bone bridge) causing orthopaedic problems such as limb length discrepancy and bone angulation deformity (Salter & Harris 1963, Ogden 2000a,b,c, Xian et al 2004, Chung et al 2006, McCarty et al 2010, Fischerauer et al 2011, Macsai et al 2011. Although a microarray gene expression study (Macsai et al 2012) and pathway-specific studies were recently reported describing changes in the levels of gene expression and potential roles of Wnt/b-catenin (Chung et al 2013a,b) and protein kinase-D (Chung et al 2013a,b) at different stages of bony repair in a rat model, the underlying pathobiology for the undesirable bony repair is unclear, and the resulting bone growth defects currently lack biological preventative treatments .…”
Section: Introductionmentioning
confidence: 99%